VOICE DISORDERS TYPES OF VOICE DISORDERS AND CAUSES (Scientific journal of the Fergana State University, 2023)
In this article, the causes of voice disorders, their types, voice changes in children and adults, Ferron’s theory of phonation, myoelastic theories prevention of voice disorders, psychological and pedagogical correctional works on voice are disclosed. Currently, voice disorders are spreading very widely, there are several opinions on the need to identify them early and carry out corrective work, as well as on prevention.